Canine-sourced Leptospirosis - Fadlul Azim Fauzi Mansur; Nurul Azmawati Mohamed @ Abd Aziz; Mohd Rahman Omar; Abdul Aziz Marwan (Japan Health Sciences University & Japan Internet, 2024)
Indexed by ERA